GENETIC DIVERSITY OF UPLAND RICE LANDRACES FROM JAVA ISLAND AS REVEALED BY SSR MARKERS - Sutoro Sutoro; Puji Lestari; Hakim Kurniawan (Indonesian Agency for Agricultural Research and Development, 2015)
Java Island is one of origins of a large number of indigenous upland rice accessions, which may serve as valuable plant genetic resources for future crop improvement in Indonesia. However, these landraces especially non-glutinous and glutinous rice are rapidly being lost because of land-use, agricultural practices and other factors. A better understanding of genetic diversity of local upland rice is important for crop improvement program, crop management and conservation strategy. This study aimed to evaluate the genetic diversity of upland rice landraces originating from Java Island. A total of 82 upland rice accessions comprising of 55 non-glutinous rice and 27 glutinous type were genotyped using the 16 simple sequence repeat (SSR) markers. The result showed that a total of 74 alleles were found with major allele frequency found on RM431 (0.96). Most of the SSR markers (56.3%) showed high discriminating power as represented by polymorphic informa-tion content (PIC) value higher than 0.5. A moderate genetic diversity index was detected in all landraces, which was 0.55. Genetic diversity index of non-glutinous and glutinous rice were 0.54 and 0.53, respectively. Their genetic distance was about 0.057. The phylogenetic tree generated two main clusters that demonstrated discrimination among landraces according to the individual genetic properties rather than their geographical origins and grain types (non-glutinous and glutinous type). The levels of genetic diversity were varied across rice types and geographical origins. According to the regions, the closest genetic distance was found between upland rice landraces from Central Java and West Java (0.040). The information derived from this study is important, in combination with phenotypic data, to identify desired useful traits came from different origins of the gene pool to be used for breeding purposes.